Narcissistic Traits and Explicit Self-Esteem: The Moderating Role of Implicit Self-View - Di Pierro, Rossella; Mattavelli, Simone; Gallucci, Marcello (Frontiers in Psychology, 2016)
Objective: Whilst the relationship between narcissism and self-esteem has been studied for a long time, findings are still controversial. The majority of studies investigated narcissistic grandiosity, neglecting the existence of vulnerable manifestations of narcissism. Moreover, recent studies have shown that grandiosity traits are not always associated with inflated explicit self-esteem. The aim of the present study is to investigate the relationship between narcissistic traits and explicit self-esteem, distinguishing between grandiosity and vulnerability. Moreover, we consider the role of implicit self-esteem in qualifying these associations. Method: Narcissistic traits, explicit and implicit self-esteem measures were assessed among 120 university students (55.8% women, Mage = 22.55, SD = 3.03). Results: Results showed different patterns of association between narcissistic traits and explicit self-esteem, depending on phenotypic manifestations of narcissism. Narcissistic vulnerability was linked to low explicit self-evaluations regardless of one’s levels of implicit self-esteem. On the other hand, the link between narcissistic grandiosity and explicit self-esteem was qualified by levels of implicit self-views, such that grandiosity was significantly associated with inflated explicit self-evaluations only at either high or medium levels of implicit self-views. Discussion: These findings showed that the relationship between narcissistic traits and explicit self-esteem is not univocal, highlighting the importance of distinguishing between narcissistic grandiosity and narcissistic vulnerability. Finally, the study suggested that both researchers and clinicians should consider the relevant role of implicit self-views in conditioning self-esteem levels reported explicitly by individuals with grandiose narcissistic traits.